Investigating the undergraduate experience of assessment in higher education - Lee, King Siong,; Hazita Azman,; Koo, Yew Lie, (Penerbit UKM, 2010)
This paper reports on the preliminary findings of a doctoral study in progress, which is situated in the context of quality in higher education, and is premised on the view that the student learning experience is ultimately the most meaningful and lasting measure of academic quality. The literature on assessment in higher education clearly places assessment at the heart of student learning and it is claimed that “the truth about an educational system” may be discovered by examining its assessment procedures (Rowntree, 1987, p.1). Using a qualitative case study approach, the study aims to reveal the values inherent in assessment, to show how these are conveyed through institutional discourses and through practices of lecturers, and how students’ learning behaviour may be affected by their perspectives of assessment. Data gathering activities for the entire doctoral research include focus group discussions and individual interviews with finalyear undergraduates, interviews with their lecturers, observations of lectures and classroom assessments, examination of documents related to the course descriptions and assessment, as well as a study of the administrative and procedural aspects of assessment which are part of the assessment praxis. The emerging themes reported here, based solely on the analysis of two of the focus group discussions, indicate how assessment praxis in higher education seems to be a reproduction of dominant power structures that have inculcated patterns of student passivity in learning.